POLITICAL PARTICIPATION HAS STRENGTHENED THE SPIRIT OF INCLUSIVENESS IN INDIAN DEMOCRACY - Fatima Akther (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2023)
The study investigates how voting affects the welcoming atmosphere of India's democratic system. The purpose of this research is to look at how voting affects the spread of democratic ideals like fairness and tolerance. The study concludes that citizens' active engagement in the political process has significantly contributed to the growth of a more welcoming atmosphere in India's democratic system. Those who are actively involved in politics are shown to be more familiar with and sympathetic to democratic ideals. A sense of personal investment in and accountability for the democratic process is fostered by voting, which in turn encourages more participation in civic life and service. Findings also show how difficult it is for people from disadvantaged backgrounds to participate in elections. Poverty, illiteracy, and discrimination are only a few examples of the structural impediments that this research shows to be in the way of people's full and equal involvement in the democratic process. The findings suggest that in order to deepen the democratic process, efforts should be made to eliminate these hurdles and promote more inclusion in political involvement. The findings of the study shed light on the importance of civic engagement in fostering diversity and inclusion in India's democratic system. The research stresses the significance of fostering a democratic culture that appreciates variety, openness, and participation.